Building Sustainable Resilience through Corporate Entrepreneurship: Insights from the Hospitality Industry - HADJ HASSINE, Abir (Revue Internationale des Sciences de Gestion, 2025)
The hospitality sector operates in an increasingly turbulent environment characterized by environmental risks, global disruptions, and complex supply chains. Traditional management approaches are insufficient to ensure organizational resilience and sustainability. This article conceptualizes Corporate Entrepreneurship (CE) as an integrative dynamic capability that simultaneously enhances organizational resilience and drives sustainability in hospitality supply chains. Drawing on an extensive theoretical review, we propose a conceptual framework in which the CE dimensions: innovation, corporate venturing, and strategic renewal, support adaptive, regenerative, and anticipatory resilience, respectively. The model also highlights the role of sustainability as both a catalyst and reinforcer of CE and resilience. Seven theoretical propositions are developed to guide future empirical research and provide managerial insights for transforming crises into sustainable opportunities. The findings emphasize that CE serves as a strategic lever for developing sustainable resilience, combining operational performance, social responsibility, and environmental stewardship.